Life on the wall: the diversity and activity of microbes on 13th – century AD. Lan Na mural painting - Sansupa, Chakriya; Suphaphimol, Nattaphon; Nonthijun, Paradha; Ronsuek, Teewararat; Yimklan, Saranphong; Semakul, Natthawat; Khrueraya, Thapakorn; Suwannarach, Nakarin; Purahong, Witoon; Disayathanoowat, Terd (Frontiers in Microbiology, 2023)
Diverse microorganisms from the three domains of life (Archaea, Bacteria and Eukaryota) cause deterioration in mural paintings worldwide; however, few studies have simultaneously targeted these three domains. This study aims to survey the microbiome and its potential for biodeterioration on unpreserved Lan Na mural paintings in Sean Khan temple, Chiang Mai, Thailand. The overview of the archaeal, bacterial, and fungal communities was reported by Illumina sequencing, whereas the 2 potential for deterioration was revealed by culturable techniques and a literature search. The abundant microbes reported in this study were also found in other ancient mural paintings worldwide.Halococcus, a salt-tolerant archaeon, as well as the eubacterial genus Crossiella dominated the prokaryotic community. On the other hand, the main fungal group was the genus Candida (Ascomycota). However, a low number of fungi and bacteria were isolated. Most of the isolates showed the ability to survive in the drought conditions of mural paintings but could not perform discoloration activities. The deterioration activity mainly affected calcium compounds, which are the main components of painting substrates. Aspergillus and several bacterial isolates could dissolve calcium compounds, but only Trichaptum species could induce crystal formation. These results suggest that deterioration of painting substrate should be taken into consideration in addition to deterioration of color in mural paintings. For the Lan Na painting in Sean Khan temple, the plaster is the prime target for biodeterioration, and thus we suggest that the preservation effort should focus on this component of the mural painting.